Phothochemical quenching is indicative of ionic stress on ‘Tahiti’ acid lime grafted on citrus genotypes - Tainá A. da Silva; Marcos E. B. Brito; Ivens H. da Conceição; Ericlis D. S. Nunes; Darvina S. Souza; Gabriel O. Martins (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective was to study the chlorophyll ‘a’ fluorescence and the photochemical quenching from ‘Tahiti’ acid lime grafted in new citrus genotypes under irrigation with three types of water during prefloration phase of the first year of cultivation, purposing to verify if the chlorophyll ‘a’ fluorescence and the photochemical quenching are indicatives of the beginning of ionic stress. An experiment was set up with three irrigation water salinity levels (0.14, 2.40 and 4.80 dS m-1), and 13 citrus rootstock, corresponding to ‘Rangpur Santa Cruz’ lime, three Citrandarins, the ‘Sunki Tropical’ mandarin and eight citrus hybrids, all grafted with the ‘Tahiti’ acid lime, using randomized block design with four replications. At 70 days after transplanting, the chlorophyll a fluorescence of the plants were evaluated. Photochemical quenching indicates begin of ionic saline stress in citrus plants; The ‘Tahiti’ acid lime grafted on TSKC x (LCR x TR) - 059, ‘Rangpur Santa Cruz’ lime, the Citrandarins ‘Riverside’ and ‘San Diego’ and TSKC x TRBK - 007 genotypes has greater activation of protective mechanisms through transient fluorescence.